PROTOTIPE ASISTENSI PENGENALAN SUARA UNTUK MANUVER KAPAL - Bayu Prasojo, Gita; Imam Firdaus, Muhamad; Nofandi, Faris; Haryanto, Tri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The rapid advancement of maritime automation through IMO's MASS framework highlights the need for voice-assisted navigation systems to enhance crew efficiency during ship maneuvering. This research aims to design a voice recognition prototype for ship steering, integrate it as an alternative control mode, and improve deck crew productivity. Employing a Research and Development (R&D) approach with prototype development, the study targeted navigation trainees and officers at Politeknik Pelayaran Surabaya (N=population during 12-month sea practice), using purposive sampling of 5 beta testers plus researcher for alpha testing. Instruments included DFRobot DF2301Q voice module, ESP32 DevKitC microcontroller, MG996R servos, potentiometer, and WS2812B LEDs, analyzed through static/dynamic tests measuring command accuracy (>90%), servo stability (35°-150°), and response time (<3s). Results demonstrated 90%+ recognition of wake word "MERATUS" and 17 navigation commands, stable servo operation, and linear sensor feedback. The prototype proves viable as MASS Level 1 decision support, reducing manual crew dependency during maneuvers.